Super-soft, firm, and strong elastomers toward replication of tissue viscoelastic response. Issue 12 (21st September 2022) - Dashtimoghadam, Erfan; Maw, Mitchell; Keith, Andrew N.; Vashahi, Foad; Kempkes, Verena; Gordievskaya, Yulia D.; Kramarenko, Elena Yu.; Bersenev, Egor A.; Nikitina, Evgeniia A.; Ivanov, Dimitri A.; Tian, Yuan; Dobrynin, Andrey V.; et al.
Abstract : Brush-like thermoplastic elastomers combine softness, firmness, strength, and damping on par with soft tissues, which is vital for biomedical device and adhesive applications. Abstract : Polymeric networks are commonly used for various biomedical applications, from reconstructive surgery to wearable electronics. Some materials may be soft, firm, strong, or damping however, implementing all four properties into a single material to replicate the mechanical properties of tissue has been inaccessible. Herein, we present the A- g -B brush-like graft copolymer platform as a framework for fabrication of materials with independently tunable softness and firmness, capable of reaching a strength of ∼10 MPa on par with stress-supporting tissues such as blood vessel, muscle, and skin. These properties are maintained by architectural control, therefore diverse mechanical phenotypes are attainable for a variety of different chemistries. Utilizing this attribute, we demonstrate the capability of the A- g -B platform to enhance specific characteristics such as tackiness, damping, and moldability.